Online Customer Review As A Purchase Decision - Riski M. Lamato; Moh. Gifari Sono (International Conference On Digital Advanced Tourism Management And Technology, 2023)
In terms of current local shoe trends, Indonesian local shoe culture has significantly changed in recent years. The purpose of this study is to investigate how consumer attitudes, through the mediation of online customer evaluations and product design, affect customers' decisions to purchase the newest local sneaker items. The research population comprised contemporary local sneaker buyers in Indonesia, and was sampled using an online survey method. The data is analyzed using the analysis path. Prior research has demonstrated that consumer attitudes, product design, and OCR have a favorable and significant impact on purchase decisions. It has been demonstrated that consumer attitudes affect how much OCR and product design influence purchases. Local shoe makers and marketers can now keep raising positive OCR and enhancing the caliber and creativity of their product designs in order to grow their market share.